Factors Influencing Student Acceptance of SIDIA E-Learning - Akbar Rizqi Alrowayyan; Ghea Sekar Palupi (Universitas Negeri Surabaya, 2026)
Digital learning platforms are widely utilized in higher education to support academic activities, yet student engagement with these systems often varies across contexts. Understanding the factors that shape continued usage therefore becomes essential. This study explores student interaction with the Sinau Digital Universitas Negeri Surabaya (SIDIA) e-learning platform by examining both user-related perceptions and system-related characteristics. Data were obtained from undergraduate students who had prior experience using SIDIA for at least one academic semester, and a quantitative analytical approach was applied. The relationships among the observed variables were evaluated using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results demonstrate that expectations regarding system usefulness and ease of operation, along with social and environmental support, contribute to the formation of user satisfaction. In addition, the quality of the system, the information it delivers, and the services supporting it play an important role in strengthening satisfaction levels. User satisfaction is further shown to influence students’ intention to continue using the platform and their actual engagement with the system. These findings indicate that satisfaction functions as a key connecting mechanism between user perceptions, system attributes, and sustained utilization of e-learning services. The study offers insights for higher education institutions in developing and managing digital learning systems that promote long-term use and effective learning support.